Modelling the Dynamics of Products and Processes Requirements. (2015) - Becattini, Niccolò; Cascini, Gaetano; Nikulin, Christopher
Abstract: This paper proposes a new modelling framework aimed at overcoming the current limitations of existing techniques for the representation of products and processes within a Technology Forecasting study. Starting from the review of the available modelling approaches, the authors define system requirements as the key elements to represent both drivers and barriers for the evolution of technical systems, analysed in the context of a business process. The new proposal allows such requirements to be mapped in an integrated and scalable model connecting finished goods with the related business processes, so as to collect the knowledge from different experts and stakeholders in a unified and manageable description, thus reducing the risks due to uncertain and partial representation. The paper presents also an example of application in the field of pharmaceutical tablet manufacturing, focusing on the industrial processes requiring the granulation of pharmaceutical powders. An in-depth discussion about the emerged criticalities supports the definition of further developments to make this approach more repeatable and suitable for Technology Forecasting methodologies.